2006
DOI: 10.1038/sj.ki.5000058
|View full text |Cite
|
Sign up to set email alerts
|

The progression of chronic kidney disease: A 10-year population-based study of the effects of gender and age

Abstract: The increase in demand for renal replacement therapy makes it important to investigate the prognosis of the earlier stages of chronic kidney disease (CKD). We examined the change in glomerular filtration rate (GFR), and patient and renal survival in CKD stage 3 in the municipality of Tromsø, a well-defined European community with a population of 58,000. All patients with estimated GFR between 30 and 59 ml/min/1.73 m(2) for more than 3 months during a 10-year study period were identified from a complete databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

39
365
6
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 482 publications
(431 citation statements)
references
References 21 publications
39
365
6
7
Order By: Relevance
“…Indeed, according to this study, GPs can be considered as a reference of care for patients in stage 3a without asking for nephrology consultation, because these patients have the same risk as the reference group (Table 4). The clinical characteristics of our patients with CKD stage 3a, in fact, show low prevalence for the main cardiorenal risk factors (i.e., albuminuria, anemia, diabetes, and CAD) with respect to more advanced stages of CKD (3b-5), and therefore, their profile is compatible with nonprogressive CKD (26)(27)(28)(29)(30). However, the suggestion of referring patients with CKD when eGFR is ,45 ml/min per 1.73m 2 is in agreement with the timing of onset of CKD-related metabolic complications (31).…”
Section: Discussionmentioning
confidence: 80%
“…Indeed, according to this study, GPs can be considered as a reference of care for patients in stage 3a without asking for nephrology consultation, because these patients have the same risk as the reference group (Table 4). The clinical characteristics of our patients with CKD stage 3a, in fact, show low prevalence for the main cardiorenal risk factors (i.e., albuminuria, anemia, diabetes, and CAD) with respect to more advanced stages of CKD (3b-5), and therefore, their profile is compatible with nonprogressive CKD (26)(27)(28)(29)(30). However, the suggestion of referring patients with CKD when eGFR is ,45 ml/min per 1.73m 2 is in agreement with the timing of onset of CKD-related metabolic complications (31).…”
Section: Discussionmentioning
confidence: 80%
“…31 (2008) Original Article Slower Decline of Glomerular Filtration Rate in the Japanese General Population: A Longitudinal 10-Year Follow-Up Study Enyu IMAI 1) , Masaru HORIO 2) , Kunihiro YAMAGATA 3) , Kunitoshi ISEKI 4) , Shigeko HARA 5) , Nobuyuki URA 6) , Yutaka KIYOHARA 7) , Hirofumi MAKINO 8) …”
Section: Hypertens Resmentioning
confidence: 99%
“…Uncontrolled blood pressure is known to be deleterious, but other factors may become more important once BP is treated 1015. Several studies have identified age,1617 male gender,17 lower initial glomerular filtration rate (GFR),1418 first–hospital-visit fasting plasma glucose18 and concomitant presence of retinopathy1920 as important risk factors for GFR decline. The proteinuria itself is a major risk factor for progression of DN 12151920.…”
mentioning
confidence: 99%